Xây dựng tài liệu nghe với sự hỗ trợ của trí tuệ nhân tạo nhằm cải thiện kĩ năng nghe tiếng Anh cho học sinh lớp 7: Một nghiên cứu tại tỉnh Gia Lai - Phan Thị Thanh Thảo, Phan Thị Thanh Thảo; Trần Thị Vũ Thiện, Trần Thị Vũ Thiện (Tạp chí Giáo dục, 2026)
Listening skills play a foundational role in the development of English proficiency, especially at the lower secondary level. In the context of digital transformation in education, the application of artificial intelligence (AI) to create personalized listening materials tailored to learners’ abilities and needs has emerged as a promising solution. Findings from the study show that at Ly Thuong Kiet Lower Secondary School (Gia Lai province), seventh-grade students still have limitations in listening skills due to the lack of suitable materials, unengaging content, and limited use of technology. The use of AIsupported listening materials significantly improved students’ listening performance: the proportion of students achieving Good and Fair levels increased, their interest and vocabulary recognition ability improved, and students rated the materials as more appropriate. Strengths such as relatable content, flexible adjustment of listening speed, instant feedback, and personalization contributed to maintaining learning motivation. The study highlights the potential for broader application of AI in developing listening practice materials for general education students, promoting personalized learning and enhancing the quality of English teaching.